Pengaruh Halal Lifestyle, Korean Wave dan Electronic Word of Mouth Terhadap Keputusan Pembelian Makanan Korea - Tazqia Amalia; Santi Lisnawati; Sofiyan Muhlisin (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to determine the influence of Halal Lifestyle, Korean Wave and Electronic Word of Mouth on Korean Food Purchasing Decisions. The dependent variable in the research is purchasing decisions, while the independent variables are Halal Lifestyle, Korean Wave and Electronic Word of Mouth. The data in this research was collected through a questionnaire distributed to Generation Z consumers who had purchased and consumed Korean food products in Bogor Regency. The research method used is quantitative. The population in this research is consumers of Korean food products, with data collected totaling 100 respondents. The data analysis tool used in this research uses SPSS 26. The results of this research show that the Halal Lifestyle, Korean Wave and Electronic Word of Mouth variables have a positive and significant effect on purchasing decisions for Korean food products. ditulis dalam bahasa Inggris dan bahasa Indonesia (kecuali artikel yang ditulis dalam bahasa Inggris) yang berisikan isu-isu pokok,